2016
DOI: 10.1159/000442674
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Postnatal Diuretics Treatment on Kidney Development and Long-Term Kidney Function in Wistar Rats

Abstract: Background: Diuretics are administered to neonates to control fluid balance. We studied whether clinical doses affected kidney development and function and whether extrauterine growth retardation (EUGR) could be a modulator. Methods: Wistar rats were cross-fostered in normal food or food restricted litters at postnatal day (PND) 2 and treated daily with 0.9% NaCl, 5 mg/kg furosemide or 5 mg/kg hydrochlorothiazide (HCTZ) up to PND 8. Kidneys were evaluated on proliferation, apoptosis and a set of mRNA target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Although torsemide-induced PGE 2 would increase renin activity (9) and thereby ANG II and aldosterone, we assume that continuous blockade of NKCC2 by torsemide promotes electrolyte loss in the neonates and provokes developmental damages. In contrast to our study, no effect of early postnatal diuretic treatment on kidney development was observed in rats in a recent study (5). However, differences in the experimental design may explain this discrepancy, because the loop diuretic furosemide was used in this study at a dosage of 5 mg•kg Ϫ1 •day Ϫ1 by single daily intraperitoneal injection.…”
Section: Discussioncontrasting
confidence: 97%
“…Although torsemide-induced PGE 2 would increase renin activity (9) and thereby ANG II and aldosterone, we assume that continuous blockade of NKCC2 by torsemide promotes electrolyte loss in the neonates and provokes developmental damages. In contrast to our study, no effect of early postnatal diuretic treatment on kidney development was observed in rats in a recent study (5). However, differences in the experimental design may explain this discrepancy, because the loop diuretic furosemide was used in this study at a dosage of 5 mg•kg Ϫ1 •day Ϫ1 by single daily intraperitoneal injection.…”
Section: Discussioncontrasting
confidence: 97%
“…Our second aim was to evaluate whether extrauterine growth restriction could modulate the potential toxicity of drug treatment. Using the rat model of litter enlargement, we have previously shown that extrauterine growth restriction results in a reduction in nephron numbers (Bueters et al, , ). From the changes noted in body weight, it is clear that a state of extrauterine growth restriction was induced, even though body weights were slightly different from the start of the study.…”
Section: Discussionmentioning
confidence: 99%